Anishchenko О.S. Increasing the competitive ability of tribotechnical solutions in the field of metal working with pressure using the theory of solving inventive problems - Аніщенко, О. С. (Problems of Tribology, 2018)
The article proposes for the processes of metal pressure treatment a new algorithm for creating technical solutions at the level of inventions using the basic elements of the theory of solving inventive problems. The article analyzes several methods and devices for metal forming. They were created on the basis of the proposed theory and algorithm and can use friction forces to achieve the goals.